High wall shear stress proximal to myocardial bridging and atherosclerosis: intracoronary ultrasound and pressure measurements. Issue 5 (May 1995) - Ge, J.; Erbel, R.; Görge, G.; Haude, M.; Meyer, J.
Abstract : BACKGROUND--Studies have shown that myocardial bridging may prevent coronary atherosclerosis and that the segment proximal to the bridge is often sclerosed. The underlying mechanism is still unknown. METHODS--Intracoronary ultrasound and pressure measurements were performed in a patient with myocardial bridging in the left anterior descending coronary artery. A 3.5 F, 20 MHz probe was used to measure the change in cross sectional area of the lumen during the cardiac cycle. Intracoronary pressure was measured with a Double tip, end mounted pressure transducer system, the catheter having two pressure sensors located at the end of the catheter 3 cm apart. Intracoronary pressure was recorded as the catheter was slowly advanced and pulled back through the left anterior descending coronary artery. RESULTS--Systolic compression of the bridge segment was clearly visualised on ultrasonography and an eccentric plaque with calcium deposit was found in the segment proximal to the bridge. The pressure in the segment proximal to the bridge (160/26 mm Hg) was higher than that of the proximal normal segment (126/68 mm Hg). The pressure distal to the bridge was 68/30 mm Hg. A highly characteristic "sucking effect" was found in the bridge segment. The pressure in the bridge segment was 102/-40 mm Hg. CONCLUSION--The pressure in the segment proximal to the myocardial bridging was higher than aortic pressure. Disturbance of blood flow and high wall stress proximal to myocardial bridging was a main contributor to the development of atherosclerosis in the segment proximal to the bridge.